Explore Gastric Lipolysis and Lipid Oxidation of Conventional versus Pasture-Based Milk by a Semi-dynamic In Vitro Digestion Model - Pinho, Susana C. M; Faria, Miguel; Casal, Susana; Sobral, M. Madalena C; Alves, Rui; Cabrita, Ana R. J; Fonseca, António J. M; Ferreira, Isabel M.P.L.V.O (Journal of agricultural and food chemistry, 2021)
Research on gastric lipolysis of commercial cow’s milk with different fatty acid (FA) compositions is scarce. Gastric lipase exhibits specificity for the sn-3 chain position of triacylglycerols, whose structure is influenced by milk FA composition. Therefore, during gastric digestion of conventional (C) vs pasture-based (P) milk, differences may occur on lipolysis, which has impact on free FA available, influencing their absorption/metabolism rate and physiological hormonal responses. Those two milk types were subjected to the INFOGEST semi-dynamic digestion model. Five gastric emptying points were analyzed for oxidative degradation of polyunsaturated fatty acids (PUFA) and individual free FA. The relative release of medium-chain FA (C8:0–C12:0) was higher than that of longer-chain FA (C14:0–C18:0), and a linear increase in markers of PUFA oxidative degradation occurred along gastric digestion. Quantitatively, C8:0, C18:2n-6, C18:3n-3, and CLAc9t11 were higher (P < 0.001) in P milk when compared with C milk.